Expanding the reach of health sciences education and empowering others: the OpenCourseWare initiative at Tufts University - Lee, Mary Y.; Albright, Susan; O'Leary, Lisa; Terkla, Dawn Geronimo; Wilson, Nancy (Tufts Archival Research Center, 2005)
OpenCourseWare (OCW) represents an innovative and cost-effective opportunity for institutions to take a more active role in strengthening health sciences education worldwide. OCW content can provide a supplement to curricula available in resource-rich settings, as well as provide much of the basic content critical to teaching and research in resource-limited health education environments. Educational institutions worldwide have the opportunity to explore how OCW and other open tools and materials can supplement efforts to build health education capacity to address global shortages of healthcare workers. Tufts University has worked to leverage open, digital resources to support medical education since 1994 with the creation of the Tufts University Sciences Knowledgebase (TUSK). This experience has yielded vital lessons for institutions interested in OCW, including: effectively motivating faculty participation; managing the inherent complexity of open publishing of health sciences content due to its rapidly evolving nature and reliance on copyrighted materials; generating support through internal and external communication throughout the process; and creating institutional systems that ensure the long-term sustainability of OCW initiatives.